2023
DOI: 10.3389/fnins.2023.1213094
|View full text |Cite
|
Sign up to set email alerts
|

SGIP1 in axons prevents internalization of desensitized CB1R and modifies its function

Abstract: In the central nervous system (CNS), cannabinoid receptor 1 (CB1R) is preferentially expressed in axons where it has a unique property, namely resistance to agonist-driven endocytosis. This review aims to summarize what we know about molecular mechanisms of CB1R cell surface stability in axonal compartments, how these impact CB1R signaling, and to consider their physiological consequences. This review then focuses on a potential candidate for maintaining axonal CB1R at the cell surface, Src homology 3-domain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In neurons and other naïve cells, CB1R-interacting proteins also bias the signaling of the receptor, for example, SH3-containing GRB2-like protein 3-interacting protein 1 (SGIP1) 24 , 25 , 38 , 39 , Cannabinoid Receptor Interacting Protein 1a and 1b (CRIP1a/b) 40 , 41 , and G Protein-Coupled Receptor Associated Protein 1 (GASP1) 42 , 43 . The situation may become yet more complex with heterodimers of CB1R 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In neurons and other naïve cells, CB1R-interacting proteins also bias the signaling of the receptor, for example, SH3-containing GRB2-like protein 3-interacting protein 1 (SGIP1) 24 , 25 , 38 , 39 , Cannabinoid Receptor Interacting Protein 1a and 1b (CRIP1a/b) 40 , 41 , and G Protein-Coupled Receptor Associated Protein 1 (GASP1) 42 , 43 . The situation may become yet more complex with heterodimers of CB1R 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, neuroligin-3 is selectively expressed at CB 1 R-expressing inhibitory synapses in the CA1 region of the hippocampus ( 60 ). Future studies may also test the possibility whether certain intracellular CB 1 R-interacting proteins, such as the Src homology 3-domain growth factor receptor-bound 2-like (endophilin) interacting protein 1 (SGIP1), Wiskott-Aldrich syndrome protein-family verprolin-homologous protein 1 (WAVE1) complex, intracellular protein BiP and growth-associated protein of 43 kDa (GAP43) may also regulate the cannabinoid tone specifically in the intrasynaptic active zone at perisomatic synapses ( 61 65 ). The cannabinoid receptor-interacting protein 1a (CRIP1a) is an especially interesting candidate, because it is present at inhibitory synapses in the hippocampus and was shown to affect tonic CB 1 R activity in cellular preparations ( 66 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 ) also indicates that residency time of CB1R at the plasma membrane is reduced by SGIP1 knockdown, suggesting that although surface levels might be restored under basal conditions, in response to an agonist, activated CB1R receptors are quickly removed from the plasma membrane. Finally, work by the Blahos and Mackie groups suggests that the presence or absence of SGIP1 can have an allosteric effect on CB1R signalling ( Durydivka et al, 2023 ; Gazdarica et al, 2022 ; Hajkova et al, 2016 ) and might therefore affect signalling in the absence of overt changes in CB1R surface levels. Further studies will be required to determine how SGIP1 loss affects CB1R localisation in specific subdomains of the axon, and exactly how SGIP1 supports CB1R-dependent Ca 2+ signalling at the presynapse.…”
Section: Discussionmentioning
confidence: 99%
“…SGIP1 has been reported to bind ctCB1R in a yeast two-hybrid study, but the site of interaction on CB1R was not determined ( Hajkova et al, 2016 ). Expression studies in HEK293 cells have suggested that SGIP1 interferes with agonist-induced internalisation of CB1R and modulates the recruitment of β-arrestin2 and GRK3, as well as downstream signalling via ERK1 and ERK2 (MAPK3 and MAPK1, respectively; collectively referred to as ERK1/2) ( Durydivka et al, 2024 , 2023 ; Gazdarica et al, 2022 ; Hajkova et al, 2016 ). Moreover, SGIP1-knockout mice display disrupted ECS-dependent behaviours and altered responses to Δ 9 -tetrahydrocannabinol (THC), including reduced anxiety, reduced acute nociception and increased sensitivity to cannabinoid-induced analgesia, while working memory and exploration remain unaltered ( Durydivka et al, 2023 ; Dvorakova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%